Crinivirus and begomovirus detection in tomato plantlets and weeds associated to nurseries - Solórzano Morales, Ántony (2017)
The aim of this work was to detect plant infections caused by Tomato chlorosis virus (ToCV) and begomovirus in tomato plantlets, and in growing weeds around nursery greenhouses. During one year, starting in April 2008, 168 leaf tissue samples were collected, 90 tomato plantlets and 78 weeds from three different nurseries in Cartago province, Costa Rica. Reverse transcription and real time polymerase chain reaction (qRT-PCR) was used to determine that 18,9% of tomato plantlets and 7,7% of weeds were infected with ToCV virus. Begomoviruses were detected using Dot Blot hybridization and non-radioactive probe. Next, hybridization results were confirmed using Rolling Circle Amplification (RCA) followed by PCR, using universal primers. None tomato plantlet resulted positive when tested, but there were six weeds infected; in fact, Phytolacca icosandra and Brassica sp. were both coinfected with ToCV virus. These results suggest that ToCV infected tomato plantlets when commercialized, could serve as way of virus introduction to other country regions. Finally, weeds growing around greenhouses have shown to be potential viral sources of ToCV and begomovirus.